Respuesta :

Answer:

Yes, it is enough

[tex]y = -3x + 16[/tex]

Step-by-step explanation:

Given

[tex]Point = (6, -2)[/tex]

[tex]m = -3[/tex]

Required

Is the given info enough to find the equation?

Yes, it is enough and the proof is as follows:

And equation is solved using:

[tex]y - y_1 = m(x - x_1)[/tex]

Where

[tex](x_1,y_1) = (6,-2)[/tex]

[tex]m = -3[/tex]

Substitute these values in [tex]y - y_1 = m(x - x_1)[/tex]

[tex]y - (-2) = -3(x - 6)[/tex]

[tex]y +2 = -3(x - 6)[/tex]

Open bracket

[tex]y +2 = -3x + 18[/tex]

Make y the subject

[tex]y = -3x + 18-2[/tex]

[tex]y = -3x + 16[/tex]

From the above, one can see that the given info is enough